2023
DOI: 10.1097/mao.0000000000003858
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomic Analysis of Otologic Surgery: Comparison of Endoscope and Microscope

Abstract: Objective: The comparative postural health of surgeons performing endoscopic and microscopic otologic surgeries has been a topic of active debate, with many nascent or anecdotal reports suggesting the latter encourages suboptimal ergonomics. Using inertial body sensors to measure joint angles, this study sought to objectively evaluate and compare the ergonomics of surgeons during endoscopic and microscopic otologic surgeries. Study Design: Prospective pilot trial. Setting: Large, multicenter, academic hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The primary benefits of the exoscope likely reside in improved ergonomics and in improved teaching capabilities. While improved ergonomics in otologic surgery with the exoscope have not been demonstrated yet, they have been demonstrated in total endoscopic ear surgery by 1) improved neck and back angles in residents and 2) lower pain levels in attendings (3). The postures utilized in exoscopic and endoscopic ear surgery are similar; thus, one may hypothesize that the ergonomics in exoscopic ear surgery will be improved as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary benefits of the exoscope likely reside in improved ergonomics and in improved teaching capabilities. While improved ergonomics in otologic surgery with the exoscope have not been demonstrated yet, they have been demonstrated in total endoscopic ear surgery by 1) improved neck and back angles in residents and 2) lower pain levels in attendings (3). The postures utilized in exoscopic and endoscopic ear surgery are similar; thus, one may hypothesize that the ergonomics in exoscopic ear surgery will be improved as well.…”
Section: Discussionmentioning
confidence: 99%
“…Type 1 tympanoplasty is a successful surgical intervention for tympanic membrane perforation that has been traditionally described with the use of an operating microscope (1). In recent years, total endoscopic tympanoplasty has become increasingly more popular with proponents touting improved visualization (2), teaching capabilities, and ergonomics (3). In multiple systematic reviews and meta-analyses, graft success rates range from 85% to 90% for both the microscopic and endoscopic approaches, and audiometric outcomes are comparable (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Previous ergonomic studies mostly concentrate on preventing musculoskeletal injury, physical burdens in endoscopy, laparoscopy [ 25 ] or robotic surgical [ 11 ]. Annie E [ 26 ] use inertial body sensors to measure joint angles to evaluate the ergonomics of surgeons during endoscopic and microscopic otologic surgeries. Our study builds upon these concepts, using the difficulty level of the operation as a starting point, and progressing from salpingectomy to ovarian cystectomy and myomectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Arrighi‐Allisan et al found resident necks and backs were more flexed when using the microscope compared to the endoscope. 5 However, the exoscope represents an even newer modality now used in Europe and Asia. Exoscopes allow for the use of 3‐dimensional (3D) cameras to magnify the surgical field and project it onto a video tower.…”
mentioning
confidence: 99%
“…Although a variety of ergonomic assessments exist, we elected to use the RULA due to its comprehensive evaluation, intuitive interpretation, and prevalence of use in previous ergonomic literature. 5 , 8 …”
mentioning
confidence: 99%